Clinical and prognostic significance of OPN and VEGF expression in patients with non-small-cell lung cancer. Issue 4 (August 2015) - Lin, Qunying; Guo, Lijing; Lin, Guosheng; Chen, Zhiwei; Chen, Tonghuan; Lin, Juan; Zhang, Bo; Gu, Xiaobin
Highlights This was the first study investigating OPN and VEGF expression in NSCLC including patients with all stages (I–IV). The present study showed the clinical significance of OPN and VEGF expression in NSCLC. NSCLC Patients with OPN(+)/VEGF(+) had the worst prognosis among groups. OPN expression and VEGF expression were independent prognostic factors for NSCLC.